Three essays in the economics of education - Ferro, Maria Margarida Caetano Rodrigues Jorge Rodrigues (2011)
This dissertation is composed by three papers, all related with child human capital accumulation. In particular, I study the role that parental time, defined as the time parents spend with children, has on this process. The main motivation for this dissertation is the general assumption made in human capital economic literature that the intergenerational transmission of human capital does not depend on the time parents spend with their children. The literature acknowledges the important role that parents have in child's development by including parental human capital in the child's human capital production function, together with other inputs, such as innate ability and formal education. However it is usually assumed that this transmission occurs automatically. This dissertation considers and tests a different assumption: that parental time affects child development. In the first chapter I take this new assumption for granted and develop a theoretical model where child's human capital production function depends on parental human capital and on parental time. The other two chapters present and discuss two different empirical tests conducted to evaluate the plausibility of the new assumption. The difference between them is the defnition of parental time: in the second chapter I define it as the number of hours during a regular day that mothers spend with their children; in the third chapter parental time is defined as the number of months after birth the child is taken care exclusively by her parents.